Predictive Value of Toll-like Receptor 4 in Peripheral Blood Mononuclear Cells in Combination with Serum Procalcitonin for Sepsis - Yuanhui HU, Dongling TANG, Pingan ZHANG (Zhongguo quanke yixue, 2022)
Background Sepsis is an infection-caused systemic inflammatory response syndrome, with relatively high morbidity and fatality rate. Early diagnosis and treatment are vital for prevention and treatment of sepsis. However, there are no simple clinical biomarkers that could rapidly and effectively detecting sepsis. Objective To assess the combined predictive value of toll-like receptor 4 (TLR4) in peripheral blood mononuclear cells and serum procalcitonin (PCT) for sepsis. Methods One hundred and ten sepsis patients (sepsis group) , 113 patients with infection but without sepsis (non-sepsis group) , and 95 healthy individuals (control group) were recruited from Renmin Hospital of Wuhan University from October 2020 to November 2021. Sepsis patients were divided into non-shock subgroup and shock subgroup according to the shock situation. Laboratory indicators, TLR4 in peripheral blood mononuclear cells and serum PCT of three groups were collected and analyzed. The quick Sepsis-related Organ Failure Assessment (qSOFA) score, infectious pathogens, and sites of infection of sepsis and non-sepsis groups were comparatively analyzed. The receiver operating characteristic curve (ROC) and area under the curve (AUC) were used to analyze the diagnostic value of TLR4 mRNA and PCT, alone and in combination, for sepsis. Results The levels of red blood cell (RBC) count, white blood cell (WBC) count, neutrophil count, hemoglobin (Hb) , hematocrit (HCT) , platelet count, alanine aminotransferase (ALT) , aspartate aminotransferase (AST) and direct bilirubin (DBiL) differed significantly across the three groups (P<0.05) . Sepsis group had significantly elevated levels of WBC count, neutrophil count, ALT, AST and DBiL, and significantly decreased levels of RBC count, Hb, HCT and platelet count compared with other two groups (P<0.05) . Sepsis and non-sepsis groups had significant difference in qSOFA score (Z=-3.128, P=0.002) . Gram-negative bacteria were the most prevalent pathogenic microorganism in both sepsis and non-sepsis groups, and lung was the most infected site. There were significant differences between the two groups in infected pathogenic microorganisms and infected sites (P=0.033, 0.003) . The levels of TLR4 mRNA in peripheral blood mononuclear cells and PCT showed a successive decrease in sepsis group, non-sepsis group and control group (P<0.01) . The TLR4 mRNA levels in peripheral blood mononuclear cells of patients with sepsis induced by gram-positive bacteria, gram-negative bacteria, fungi and other pathogens in sepsis group were 0.154 (0.302) , 0.139 (0.493) , 0.119 (0.206) and 0.151 (0.336) , respectively, with no significant differences (H=0.378, P=0.945) . The level of TLR4 mRNA differed significantly between shock subgroup (n=75) 〔0.210 (0.330) 〕 and non-subgroup hose without (n=35) 〔0.118 (0.323) 〕 (Z=1.473, P=0.026) . For the prediction of sepsis, the AUC of TLR4 mRNA level was 0.813, with sensitivity of 80.00%, specificity of 68.97% and Youden index of 0.489 7, when the optimal cutoff value was defined as 0.056; the AUC of PCT was 0.818, with sensitivity of 87.63%, specificity of 75.94% and Youden index of 0.635 6, when the optimal cutoff value was defined as 0.070 μg/L; the AUC of TLR4 mRNA combined with PCT was 0.888, with sensitivity of 68.04%, sensitivity of 93.10% and Youden index of 0.611 4. Conclusion Multiple routine blood indicators and biomarkers abnormalities were found in sepsis patients. TLR4 mRNA level was associated with the severity of sepsis. TLR4 mRNA in peripheral blood mononuclear cells and serum PCT could be used as auxiliary predictors of sepsis, the combination of TLR4 mRNA and PCT could improve the predictive efficiency in sepsis, indicating a high clinical application value.